Wearables for continuous patient monitoring on COVID-19 isolation wards - Roman, C; Vollam, S; Watkinson, P; Tarassenko, L (IEEE, 2023)
An ambulatory monitoring system for the continuous monitoring of heart rate, respiratory rate and oxygen saturation, using wearable devices was implemented at the start of the COVID-19 pandemic on selected isolation wards in a large UK hospital. We have retrospectively analysed the data and nurse observations from two groups of patients on these wards: those whose care was escalated so that they were admitted to the Intensive Care Unit (ICU); and those who were discharged home or to a non-isolation ward (stepping down). The computation of population averages for these two groups 24h prior to an ICU admission or prior to stepping down provides evidence for the value of wearable monitoring for the early identification of physiological deteriorations in COVID-19 patients. The continuous data from the finger-worn pulse oximeter reveals clinically significant changes between 2 and 3 hours ahead of the regular vital-sign observations by the nursing staff. We also show how a hybrid score based on six physiological parameters (calculated from a mixture of continuous and intermittent vital-sign data) can provide early warning of deterioration for high-risk patients.